Health Promotion and Health Education Developed from Schools as a Key Tool for Health Interventions - Monsalve Lorente, Laura (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
Promotion and Health Education developed from Schools is one of the key tools of health interventions. Access to children and young people is almost complete because of the obligatory education. In the period of the obligatory people education are more receptive for the learning, being the period of the vital development in which acquire major life habits that are consolidated with the years (physical activity, food, etc.) It also is an area of social intervention that counts with health workers who have high qualifications from the pedagogical point of view. In this context, the main objective of ESP is to develop activities and encourage the students to achieve the highest attainable standard of health, through the acquisition of knowledge and skills that promote choice and adoption of healthy lifestyles, seeking the participation, the interaction and social integration and the ability to work critically and creatively, and the search for solutions. Schools, along with the home are two of the key places where takes place the individual and social development of people in its early stages, exerting an important role in shaping behavior and social values of children, adolescence and youth. The achievement of positive educational outcomes in the teaching centers closely related to the achievement of good health among students. According to this reality, schools have the need to include addressing the issues related to health promotion as one of the foundations that will enable them to achieve educational goals.